A distributed event-triggered algorithm for optimisation problem with a designable minimum inter-event time - Yang, Zhiqiang; Wei, Mengli; Ji, Qiutong; Zhao, Zhongyuan (2022 37th Youth Academic Annual Conference of Chinese Association of Automation (YAC), 2022)
Aiming at the optimization problem of multi-agent systems, a zero-gradient-sum optimization algorithm based on event-triggered control is designed to reduce the update frequency of controller and the communication burden between agents. Under the proposed distributed optimization algorithm, the states of all agents asymptotically converge to the global optimal value without using any global information. In addition, Zeno behavior can be avoided, and the minimum inter-event time can be designed. Simulation results verify the effectiveness of the proposed algorithm.